2014
DOI: 10.1002/bmc.3318
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid profiles of immature and mature fruit tissues of Citrus grandis Osbeck (Dangyuja) and overall contribution to the antioxidant effect

Abstract: Citrus fruits are a valuable functional food and their peel is used in East Asian folk medicine. In this study, the polar components of the fruit tissues of Citrus grandis Osbeck were analyzed using high-performance liquid chromatography-tandem mass spectrometry and compared with reported data. Among the 13 characterized compounds, eight flavonoids and one coumarin were identified for the first time in fruit tissues. The total amount of the identified components was the largest for the immature fruit peel, fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In this study, a widely targeted metabolomic approach combined with transcriptome data was used to explore flavonoid accumulation and its underlying molecular regulation in SOPs under magnesium stress. Although previous studies had explored the flavonoid pathway in citrus, the number of flavonoid components identified remained limited (Yu et al, 2015;Wang et al, 2019;Yu et al, 2022). In our study, we identified 740 flavonoid components in SOPs, representing a significant supplement to the previous work.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, a widely targeted metabolomic approach combined with transcriptome data was used to explore flavonoid accumulation and its underlying molecular regulation in SOPs under magnesium stress. Although previous studies had explored the flavonoid pathway in citrus, the number of flavonoid components identified remained limited (Yu et al, 2015;Wang et al, 2019;Yu et al, 2022). In our study, we identified 740 flavonoid components in SOPs, representing a significant supplement to the previous work.…”
Section: Discussionmentioning
confidence: 65%
“…The peak at m/z = 465.14 ( Fig. 3b) was assigned as hesperetin 7-O-glucoside based on previously reported flavonoid profiles for Citrus grandis [32]. This is the first time that hesperetin 7-O-glucoside has been detected as a major constituent in grapefruit peel.…”
Section: ) and This Shows [M + H -H 2 O] + For L-threonine And [M + H]mentioning
confidence: 66%
“…The most abundant flavonones are naringin, naringenin, neoeriocitrin and neohesperidine. 31 , 64 , 66 69 The presence of common flavonoids like: hesperidin, neohesperidin, naringenin, naringin and rutin are determined at high amount in Citrus grandis juice. 44 , 70 In an extraction condition for 1 and 3 hours at 50°C, the total yield of total flavonoid content from the peels of Citrus grandis extracted by aqueous methanol extract (80:20 v/v, methanol: water) were 149.05mg/L and 158.09mg/L.…”
Section: Phytochemistrymentioning
confidence: 99%
“…40,44,51 Limonoids from Citrus grandis seeds, particularly limonin and nomilin reported chemo preventive bioactivities, specifically free radical-scavenging. 31,129 and glutathione S-transferaseinducing activity. Methanolic extract of Citrus grandis administered by intraperitoneal route demonstrated to increase the longevity of non-viable tumor cell and their count count and decrease the volume of tumor.…”
Section: Anticancer Potentialsmentioning
confidence: 99%